GAMBARAN SIKAP TERHADAP KEBISINGAN PADA SISWA SMK NEGERI 2 MANADO - Raintung, Haidy Febrian; Mengko, Steward K.; Dehoop, Julied (Universitas Sam Ratulangi, 2014)
Abstract: Hearing loss is the inability of a person’s sense of hearing in listening range of sound that can still be heard by people with normal hearing. With the growing popularity of entertainment venues (discos, karaoke, music concerts, internet cafes, etc.) as well as the use of portable music player, leisure noise have become the primary source that causing increased incidence of adolescent noise induced hearing loss (NIHL). Attitudes towards noise needs to be assessed at a young age, this is because the attittude is the basis of behavior, and behavior (towards leisure noise) can affect the amount of noise exposure of each person. Chronicity of NIHL symptoms often make adolescent tends to ignore the serious long-term problem that can arise and not take steps to resolve it. Objective: The purpose of this study is to obtain data from students of Manado 2nd Vocational Senior Secondary School concerning attitudes towards noise. Method: This research used descriptive observational with cross-sectional study. The subjects are students of Stone Concrete’s majors in Manado 2nd Vocational Senior Secondary Schoolthat have passed initial hearing screening. Result: Of the 20 respondents who willingly take part in this research, obtained 5 respondents (25%) had negative attitude, 10 respondents (50%) had neutral attitude, and 5 respondents (25%) had positive attitude. From audiometric examination, obtained 4 respondents had a mild decreased in hearing threshold. Of the 4 respondents, 2 (50%) of them had a neutral attitude and 2 other respondents (50%) had positive attitude. Conclusion: Respondents with positive attitude towards noise are vulnurable to hearing threshold changes caused by daily noise exposure.Keywords: adolescent, hearing, noise, attitudes towards noise Abstrak: Gangguan pendengaran merupakan ketidakmampuan indra pendengaran seseorang dalam mendengarkan rentang suara yang masih dapat didengar oleh orang dengan pendengaran normal. Semakin berkembangnya popularitas dari tempat-tempat hiburan (diskotik, karaoke, konser musik, warung internet, dan lain sebagainya) serta penggunaan pemutar musik portabel telah menjadi sumber peningkatan angka kejadian gangguan pendengaran akibat bising (GPAB) pada usia muda. Sikap terhadap kebisingan perlu dinilai pada usia muda, hal ini dikarenakan sikap merupakan dasar dalam berperilaku, dan perilaku (terhadap kebisingan sosial) dapat mempengaruhi derajat paparan bising masing-masing orang. Kronisitas dari gejala (GPAB) membuat kaum muda kurang menanggapi serius masalah-masalah jangka panjang yang dapat ditimbulkan, serta mengambil langkah untuk mengatasinya. Tujuan: Tujuan penelitian ini adalah untuk memperoleh data sikap terhadap kebisingan pada siswa sekolah menengah kejuruan (SMK) Negeri 2 Manado. Metode Penelitian:Penelitian ini merupakan penelitian deskriptif observasional dengan menggunakan metode cross-sectional. Subjek penelitian adalah siswa jurusan Teknik Konstruksi Batu Beton (TKBB) SMK Negeri 2 Manado yang sudah melewati screening pendengaran awal. Hasil: Dari 20 responden yang bersedia menjadi responden penelitian, didapatkan 5 responden (25%) mempunyai sikap negatif, 10 responden (50%) mempunyai sikap netral, dan 5 responden (25%) mempunyai sikap positif. Dari pemeriksaan audiometrik, didapatkan 4 responden mengalami penurunan ambang dengar derajat ringan. Dari 4 responden tersebut, 2 (50%) diantaranya mempunyai sikap netral dan 2 responden (50%) mempunyai sikap positif. Simpulan: Responden yang bersikap positif terhadap bising (pro-bising) rentan terhadap terjadinya perubahan ambang dengar yang akibatkan oleh paparan kebisingan sehari-hari.Kata kunci: usia muda, pendengaran, bising, sikap terhadap kebisingan